Current problems and issues for maize cultivation in Ukraine - Ovechko, K. (ТДАТУ, 2018)
At present Ukraine has reached the maximum level of maize cultivation: over the past 15 years, our farmers have improved the technology of its growing, which resulted in yield doubled - to 66 centners per hectare. However, in comparison with the European level, it remains low, where the average yield is 120 pounds. All of these problems and issues must be solved by further cultivation technologies improving, but this requires substantial investment.
Keywords: Ukraine; cereal crop; number of industrial products; European countries